EVALUASI KINERJA ANGKUTAN UMUM PENUMPANG KOTA MALANG PADA JALUR GA (HAMID RUSDI - ARJOSARI) - Tri Asmaraning Tyas A M; Alik Ansyori (Media Teknik Sipil, 2014)
EVALUASI KINERJA ANGKUTAN UMUM PENUMPANGKOTA MALANG PADA JALUR GA(HAMID RUSDI - ARJOSARI)Tri Asmaraning Tyas A M1, Alik Ansyori,21,2Jurusan Teknik Sipil Fakultas Teknik – Universitas Muhammadiyah MalangAlamat korespondensi : Jalan Raya Tlogomas 246 Malang 65144 alik.syah@yahoo.comABSTRACTPublic transport passengers in Malang commonly called public transportation or public transitis on of the means of transport that is often used by people to perform daily activities - day, butpublic transport passengers in the city of Malang is now often seen to cause problems and distrupttraffic. The purpose of this study was to determine the level of service of public transport passangersGA pathway. The method used is the empirical methods that include surveys of static and dynamicsurvey. The results of the performance study of public transit passanger load factor pathway GAearned an average of 189,15 %,the average frequency of 62 kend / h, average time headway of 1,0minutes, average travel speed of 16,44 km/h.Keywords : Performance Evaluation of Public Transport Passengers